2015
DOI: 10.1080/21645515.2015.1056951
|View full text |Cite
|
Sign up to set email alerts
|

A significant and consistent reduction in rotavirus gastroenteritis hospitalization of children under 5 years of age, following the introduction of universal rotavirus immunization in Israel

Abstract: Universal rotavirus vaccination with RotaTeq was introduced in Israel in December 2010. We examined hospitalization rates of children under 5 years of age due to all-cause and rotavirus gastroenteritis, both before and 3 years after universal introduction of the vaccination. An ongoing hospital-based surveillance network that was established in November 2007, accessed information regarding hospitalization of children due to gastroenteritis (n D 6205) in 3 hospitals in northern Israel, with an annual average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…This percentage was similar before and after the introduction of universal rotavirus immunization in Israel. A substantial 62% reduction was evident in the incidence of rotavirus gastroenteritis hospitalizations during the universal immunization years [26][27][28] compared to the preuniversal immunization years, but rotavirus remained the leading cause of gastroenteritis hospitalizations, being detected in 40.2% and 20.0% before and after the introduction of universal immunization. The coverage of three doses of rotavirus vaccine in Israel is estimated at~80%, 29 which together with good vaccine effectiveness 30 explain the reduction in hospitalizations for rotavirus gastroenteritis.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This percentage was similar before and after the introduction of universal rotavirus immunization in Israel. A substantial 62% reduction was evident in the incidence of rotavirus gastroenteritis hospitalizations during the universal immunization years [26][27][28] compared to the preuniversal immunization years, but rotavirus remained the leading cause of gastroenteritis hospitalizations, being detected in 40.2% and 20.0% before and after the introduction of universal immunization. The coverage of three doses of rotavirus vaccine in Israel is estimated at~80%, 29 which together with good vaccine effectiveness 30 explain the reduction in hospitalizations for rotavirus gastroenteritis.…”
Section: Discussionmentioning
confidence: 97%
“…Herd immunity possibly explains the 36% reduction in the incidence of rotavirus gastroenteritis hospitalizations in children aged 24-59 who were not eligible for a rotavirus vaccine in the framework of the universal vaccination program. 27,28,31 A 1-y study after the introduction of universal rotavirus immunization in Finland showed that norovirus was detected in 25% of children aged less than 15 y with acute gastroenteritis (both inpatient and outpatient settings), while rotavirus was found in 24%. 22 In agreement with our findings, a reduction in rotavirus gastroenteritis was observed after introducing universal rotavirus immunization compared to the preceding period in Finland, however, as in our study, the percentage of norovirus gastroenteritis was similar between the two periods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations